2012
DOI: 10.1016/j.jaci.2011.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Asthma diagnosis and airway bronchodilator response in HIV-infected patients

Abstract: Background Despite the high prevalence of respiratory symptoms and obstructive lung disease in HIV-infected persons, the prevalence of bronchodilator reversibility (BDR) and asthma has not been systematically studied during the era of combination antiretroviral therapy (ART). Objective To determine the prevalence of asthma diagnosis and related pulmonary function abnormalities in an HIV-infected cohort and to identify potential mechanisms. Methods A cross-sectional analysis of 223 HIV-infected individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 51 publications
4
62
2
Order By: Relevance
“…Researchers in one study found an association between HIV-positive patients with prior pneumonia with either PC or a bacterial pathogen and doctor-diagnosed asthma (56). A second study of HIVpositive individuals demonstrated that history of PC was associated with an obstructed spirometric pattern in lung function testing (57).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in one study found an association between HIV-positive patients with prior pneumonia with either PC or a bacterial pathogen and doctor-diagnosed asthma (56). A second study of HIVpositive individuals demonstrated that history of PC was associated with an obstructed spirometric pattern in lung function testing (57).…”
Section: Discussionmentioning
confidence: 99%
“…First, eosinophilia in the bronchoalveolar lavage fluid of HIV-positive patients with Pneumocystis pneumonia has been well documented; however, whether a correlation exists between high eosinophil counts and lower Pneumocystis burden in these patients is unknown (32, 33). Secondly, patients with a history of Pneumocystis or bacterial pneumonia had a significantly higher rate of physician-diagnosed asthma, a disease that has a well-established eosinophilic component in regards to pathogenesis (34). Murine models of Pneumocystis have also shown STAT6, a transcription factor required for Th2 responses, is necessary for the development of airway hyperresponsiveness early in the course of infection (23).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the majority of asthma diagnoses in the general population occurs in children (50). Doctor-diagnosed asthma was associated with female sex, obesity, not being on cART during the study period, and a history of bacterial or Pneumocystis pneumonia (47). In addition, approximately 10% of the cohort had high sputum eosinophil counts, and there was an association between doctor-diagnosed asthma or bronchodilator response and high sputum eosinophil counts, but the majority of participants with doctor-diagnosed asthma or bronchodilator response did not have elevated sputum eosinophils, suggesting that there may be non-T helper type 2-related mechanisms causing asthma in HIV.…”
Section: Obstructive Lung Disease: Associations With Hivmentioning
confidence: 87%
“…In the Veterans Aging Cohort Study, a predominantly smoking older male cohort, asthma diagnosis was similar between individuals with and those without HIV (41). Two recent studies with a broader population of individuals with HIV have found that 11 and 21%, respectively, have an asthma diagnosis by history (doctor-diagnosed asthma) (46,47). These prevalence estimates may be greater than the estimated prevalence of approximately 7.6% in the general population (48).…”
Section: Obstructive Lung Disease: Associations With Hivmentioning
confidence: 99%
See 1 more Smart Citation